2010
DOI: 10.5194/nhess-10-2653-2010
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation on the Ismetpasa segment of the North Anatolian Fault after the Golcuk <i>M</i><sub>w</sub> = 7.4 and Duzce <i>M</i><sub>w</sub> = 7.2 shocks

Abstract: Abstract. The Ismetpasa segment of the North Anatolian Fault (NAF) is a rare place where aseismic fault slip (creep) has been observed. Its creep behaviour has been monitored using different observation methods since the 1950s. The findings obtained from the studies until 1990s showed that the creep rate exponentially decreased before the major shocks in 1999, Golcuk (M w = 7.4) and Duzce (M w = 7.2). After these shocks, three GPS periods observation in 2002, 2007 and 2008 were carried out on the geodetic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…However, some authors have claimed significant changes in rate based on the apparent outliers evident in Figure b. These are labeled K8 [ Kutoglu et al ., ] and K10 [ Kutoglu et al ., ] that we now briefly discuss. The two time intervals with high velocities recorded are 5 and 6 years duration with velocities of 12.0 ± 1.3 and 15.1 ± 4.1, respectively, preceded by a contiguous 10 year interval with 6.7 ± 1.1 mm/yr velocity (K6), suggesting an acceleration in slip rate in the interval 1992–2008 (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some authors have claimed significant changes in rate based on the apparent outliers evident in Figure b. These are labeled K8 [ Kutoglu et al ., ] and K10 [ Kutoglu et al ., ] that we now briefly discuss. The two time intervals with high velocities recorded are 5 and 6 years duration with velocities of 12.0 ± 1.3 and 15.1 ± 4.1, respectively, preceded by a contiguous 10 year interval with 6.7 ± 1.1 mm/yr velocity (K6), suggesting an acceleration in slip rate in the interval 1992–2008 (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this earthquake may have locally shifted the control points analyzed by Kutoglu et al . [, , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first measurements of aseismic creep along this section of the fault were made by Ambraseys [1970], who estimated a creep rate of ∼20 mm/yr near the town of Ismetpasa. Although it is not known whether the fault was creeping before the 1944 earthquake, numerous studies have shown that the surface creep rate follows an exponential decay through time to a current steady state value of ∼8 mm/yr [e.g., Cakir et al, 2005;Kutoglu et al, 2010;Kaneko et al, 2013;Cetin et al, 2014], implying that aseismic creep was initiated as postseismic deformation following the large earthquake. Cetin et al [2014] also showed that aseismic surface creep can, to some extent, be correlated with the geology along the North Anatolian Fault.…”
Section: Fault Creepmentioning
confidence: 99%
“…Ambraseys [1970] estimated a fault creep rate of ∼20 mm/yr for the time period [1955][1956][1957][1958][1959][1960][1961][1962][1963][1964][1965][1966][1967][1968][1969]. Since this original investigation, the fault creep has been the focus of numerous geodetic studies [e.g., Cakir et al, 2005;Kutoglu et al, 2010;Karabacak et al, 2011;Ozener et al, 2013;Cetin et al, 2014]. Cetin et al [2014] suggested that the fault creep rate has been decaying since the first measurements in 1970 to a current steady state value of ∼6-8 mm/yr.…”
Section: Introductionmentioning
confidence: 99%